Exploring Marzano Higher-Order Thinking Skills: Demographic Disparities among Technical Students - Hamdan, Nuraffefa; Yee, Mei Heong; Masran, Saiful Hadi; Tee, Tze Kiong; Eddy Sutadji; Fuada, Syifaul (Journal of Technical Education and Training, 2024)
Higher-order thinking skills (HOTS) encompass the capacity to apply knowledge, skills, and values in comprehending, reflecting, solving problems, making decisions, innovating, and creating new ideas. These skills vary among individuals, especially in learning contexts, problem-solving, and product design. The goal of this study is to evaluate technical students’ perceptions of their mastery of Marzano’s Higher Order Thinking Skills. A total of 351 students, including those from Civil, Mechanical, and Electrical Engineering programs at Sultan Abdul Halim Muad’zam Shah Polytechnic, were randomly chosen as participants. This research employed a survey design with a quantitative approach, and data were analyzed using SPSS software, with results presented in terms of means, frequencies, and percentages. Findings suggest that overall, students’ mastery of Marzano HOTS remains at a generally low level, except for four specific skills—analyzing error, constructing support, abstracting, and analyzing perspectives—which are rated at an intermediate level. On the contrary, nine HOTS areas were identified as being at a low level. An ETA analysis revealed a minimal positive correlation between Marzano HOTS mastery and variables such as gender, age, field of study, and year of study. Furthermore, no statistically significant differences were found in HOTS levels based on gender, age, and year of study. These outcomes suggest that students need further development in HOTS to better tackle learning challenges. The study also offers key insights that could assist TVET practitioners in developing more effective curricula and interventions for improving higher-order thinking skills among technical students.